Body composition changes in NCAA division I female soccer players throughout collegiate playing career - Pickler, M. C.; Gallucci, A. R.; Lee, K. M.; Bolden, L. K.; Rash, E. R.; Tinsley, G. M. (The Journal of Strength and Conditioning Research, 2025)
Body composition changes commonly occur in athletes because of fluctuations in nutrition, training regimens, and overall health. Although some studies have examined body composition changes across seasons or positions in collegiate athletes, few have analyzed these changes during the course of an entire collegiate playing career. This study addresses this knowledge gap through the analysis of body composition changes in NCAA Division I female soccer players during the course of their collegiate career. Three to 4 total body dual-energy X-ray absorptiometry scans were performed on athletes each year from 2010 to 2022, and analyses of body composition changes were conducted using linear mixed-effects models in all athletes with >2 individual scans (ALL analysis; n = 115-116) and in those with =3 years of scans (3Y analysis; n = 33-34). Statistical significance was accepted at p = 0.05. In both analyses, athletes experienced significant increases in body mass, lean soft tissue, fat-free mass, fat-free mass index, and spine bone mineral density. In the ALL analysis only, decreases in body fat percentage and increases in total bone mineral density were observed. In addition, goalkeepers had higher body mass and fat mass than those in other positions in the ALL analysis, but the 3Y analysis yielded no statistically significant differences between player positions. In conclusion, active participation in NCAA Division I women's soccer resulted in increased total lean soft tissue, fat-free mass, and bone mineral density of the spine, with participation =3 years additionally reducing body fat percentage and increasing total bone mineral density.